Sinonasal angiomatous polyp: a case report - Dhingra, Preeti; Palapalle, Naresh; Poyyil, Dilroop K.; Katna, Rakesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Sinonasal angiomatous polyp (SAP) is a rare variant of sino-nasal polyp. Sinonasal inflammatory polyps are classified histo-pathologically into 5 types: edematous, glandular, fibrous, cystic and angiomatous. They present with various different patterns and clinical features like epistaxis, nasal discharge, nasal blockage and characterised histo-pathologically by presence of prominent dilated capillary-type blood vessels. It constitutes about 4-5% of all nasal polyps. They usually present as a unilateral, painless, soft, gelatinous, translucent and polypoidal mass in nasal cavity. These polyps can grow rapidly and aggressively causing erosion of bone and severe bleeding like a cancerous lesion, making difficult to differentiate it from malignant lesion. Various differential diagnosis of SAP include inflammatory polyp, haemangioma, mucocele, fungus ball, inverted papilloma, juvenile naso-pharyngeal angiofibroma, and malignant tumors like squamous cell carcinoma, adenoid cystic carcinoma, and melanoma MRI is considered better than CT scan for diagnosis. Treatment of choice is endoscopic surgical excision with restoration of sinus drainage. .